6 RV function deteriorates earlier than LV function and predicts adverse cardiovascular outcomes. (March 2019) - Raman, Betty; Chan, Kenneth; Sivalokanathan, Sanjay; Ariga, Rina; Smillie, Robert; Ormondroyd, Elizabeth; Watkins, Hugh; Neubauer, Stefan; Mahmod, Masliza
Abstract : Background: The current assessment of hypertrophic cardiomyopathy (HCM) places emphasis on left ventricular (LV) function which is usually preserved in early disease. There are limited data on right ventricular (RV) assessment in HCM, progressive functional changes, and impact of RV dysfunction on clinical outcomes. Objectives: To examine the natural history of RV functional changes (ejection fraction and strain) and investigate its prognostic role in HCM. Methods: 311 patients (mean age 52±15 years) with HCM and preserved LV function (ejection fraction; EF ≥50%) underwent cardiac magnetic resonance (CMR) imaging and were compared to age- and sex- matched healthy controls (n=30). In 71 patients, follow-up CMR imaging was further undertaken at a median interval of 5.3 years. All patients were followed up for a composite endpoint of adverse cardiovascular outcomes, including new-onset atrial fibrillation, ventricular arrhythmia, hospitalisation due to heart failure or embolic events, or cardiovascular death. Results: HCM patients exhibited lower RV ejection fraction (RVEF) and global peak systolic strains (radial/circumferential/longitudinal) on feature-tracking analysis of cine images than healthy controls. On follow up CMR imaging, RVEF, peak RV circumferential and longitudinal strains decreased over time while LVEF remained preserved. All patients were followed up clinically for a median duration of 4.4 years. Both reduced RVEF and RV longitudinal strain were independent predictors of ventricular arrhythmias and composite cardiovascular endpoint (arrhythmia, cardiac hospitalisation and cardiovascular death), after adjusting for baseline NYHA class, medication use, maximal LV wall thickness, and late gadolinium enhancement. Patients with RVEF <55% had a 3-fold increase in ventricular arrhythmias (HR 3.03, 95% CI 1.63 to 5.66, figure 1A ) and a 2-fold increase in composite cardiac events (HR 2.05, 95% CI 1.23 to 3.41, figure 1B ). Similarly patients in the lowest quartile of RV longitudinal strain (>−16.3%) demonstrated a higher risk of ventricular arrhythmias (HR 2.20, 95% CI 1.20 to 4.01, figure 1C ) and composite cardiac events (HR 2.49, 95% CI 1.61 to 3.84, figure 1D ) compared to others. Conclusions: Despite preserved LVEF, RVEF and strain decline over time in HCM. RVEF and strain predict the occurrence of adverse cardiovascular outcomes and may have a role in prognostic risk stratification in HCM.